Implications of Public Finances Sustainability on the Consumption of Renewable Energy in EU Countries (Acta Universitatis Danubius. Œconomica, 2022)
The study analyses the implication of governments in providing financial support for the growth of the renewable energy sector, reveals some aspects of novelty, by analysing the relationship between the specific framework of sustainable public finances, the spectrum of fiscal measures capable of influencing renewable energy consumption and explore the fiscal-budgetary incentives to support the transition to renewable energy consumption. The paper generates awareness for policymakers and retrospective analysis the status of public grants and development funding as well as provides insights to improve financial support for renewable energy without increasing the number of public funds.